Harmonization Of State Administrative Court Law And Other Laws Concerning The State Administrative Courts Exclusive Authority - Nurwigati (Universitas Islam Indonesia, 2022)
This study describes and analyzes the urgency of harmonizing the exclusive authority of State Administrative Court as stipulated in the State Administrative Court Law and Non-State Administrative Court Law, and how to do this harmonization in relation to the implementation of legality principles, the theory of hierarchical regulations, and laws on the establishment of laws and regulations. As normative research using statutory and conceptual approaches, this research used a descriptive qualitative analytical method. It is expected that the results of this research can contribute to the development of Constitutional law and State Administrative Law, as well as to contribute ideas to policymakers in making and formulating various regulations related to appropriate methods to overcome disharmony in regulating the exclusive authority of the State Administrative Court to ensure that the law issued on the exclusive authority of the State Administrative Court meets society’s needs for good laws and regulations. This study concluded the following points: first, it is necessary to harmonize the State Administrative Court Law and laws other than State Administrative Court on the exclusive authority of the State Administrative Court to avoid any overlap to ensure harmonization of the laws. Secondly, the usual drafting method is more appropriate than the omnibus method because we only need to amend the State Administrative Court Law, while the other laws remain unamended.Keywords: harmonization, exclusive administrative court authority, state administrative court law Harmonisasi Undang-Undang Peratun Dan Undang-undang Lainnya Mengenai Kewenangan Eksklusif Peradilan Tata Usaha Negara AbstrakKajian ini mendeskripsikan dan menganalisis urgensi harmonisasi kewenangan eksklusif PTUN sebagaimana diatur dalam UU PTUN dan UU PTUN, serta bagaimana harmonisasi tersebut dalam kaitannya dengan penerapan asas legalitas, teori peraturan hirarkis, dan undang-undang tentang pembentukan undang-undang dan peraturan. Sebagai penelitian normatif dengan pendekatan perundang-undangan dan konseptual, penelitian ini menggunakan metode deskriptif analitis kualitatif. Hasil penelitian ini diharapkan dapat memberikan kontribusi bagi perkembangan hukum Tata Negara dan Hukum Tata Negara, serta dapat memberikan sumbangsih pemikiran kepada pembuat kebijakan dalam membuat dan merumuskan berbagai peraturan terkait dengan cara yang tepat untuk mengatasi disharmoni dalam mengatur kewenangan eksklusif DPR. Peratun untuk memastikan bahwa undang-undang yang dikeluarkan atas kewenangan eksklusif Peratun memenuhi kebutuhan masyarakat akan peraturan perundang-undangan yang baik. Kajian ini menyimpulkan beberapa hal sebagai berikut: pertama, diperlukan harmonisasi UU Peratun dengan undang-undang selain Peratun yang menjadi kewenangan eksklusif PTUN agar tidak terjadi tumpang tindih untuk menjamin harmonisasi undang-undang. Kedua, metode penyusunan biasa lebih tepat daripada metode omnibus karena kita hanya perlu mengubah UU Peratun, sedangkan undang-undang lainnya tetap tidak berubah.Kata Kunci: harmonisasi, kewenangan PTUN eksklusif, hukum PTUN